Effect of Pinching and Salicylic Acid Application on Flower and Seed Production in Larkspur (Delphinium ajacis L.) (Plant Bulletin, 2025)
Delphinium ajacis L. (Larkspur) is a widely cultivated ornamental plant valued for its vibrant inflorescences and use in cut flower production. To enhance its growth, flowering, and seed yield, a study was conducted using a Randomized Complete Block Design (RCBD) with a factorial arrangement of two factors: salicylic acid (0, 100, 150, and 200 mg L⁻¹) and pinching treatments (no pinching, 1-inch, and 2-inch pinching). A total of 12 treatments were replicated three times. The analysis revealed that both salicylic acid and pinching had a significant influence on plant performance (p < 0.01). The highest concentration of salicylic acid (200 mg L⁻¹) resulted in the earliest flowering (112.2 days), tallest plants (104.3 cm), highest number of capsules per plant (51.5), branches (10.8), spike length (34.9 cm), and seed weight per plant (21.6 g). Among pinching treatments, 2-inch pinching produced the highest number of branches (11.7), capsules per plant (46.6), and seed weight (23.9 g), though with reduced plant height (77.6 cm). These results suggest that applying 200 mg L⁻¹ salicylic acid combined with 2-inch pinching significantly enhances the vegetative and reproductive performance of Delphinium ajacis under the agro-climatic conditions of Peshawar.
Keywords: Delphinium ajacis; Pinching; Salicylic acid; Flower; Seed Production